ANALYSIS OF LACUNAR UNITS IN UZBEK, RUSSIAN AND ENGLISH LANGUAGES FROM A LINGUOCULTUROLOGICAL PERSPECTIVE - Rahmadjonov Shahzodbek Shodiboyzoda (Modern American Journals, 2025)
This article analyzes the linguoculturological features of lacunar units in Uzbek, Russian and English languages. Lacunar units are lexical or semantic gaps that exist in one language but are present in another, and are closely tied to the culture and mentality of that language community. The study explores the semantic spheres of national-cultural units found in the three languages, the reasons for the absence of equivalents, the difficulties that arise in the translation process, and the strategies of compensation. Lacunas become more evident when different cultures are contrasted, turning them into an essential indicator reflecting the uniqueness of each language. Based on modern approaches in linguoculturology, cognitive linguistics, contrastive analysis and translation studies, the article examines the functional nature, communicative significance and role of lacunar units in the educational process. The research results are significant for developing multilingual competence in primary education, preparing learners for intercultural communication and enhancing translation competence.
Keywords: Lacunarity, linguoculturology, national-cultural units, equivalence, cognitive approach, translation process, intercultural communication, semantic gap.